Pategra´ s cheese as a suitable carrier for six probiotic cultures - Bergamini, Carina Viviana (2010)
he viability of five single-strain and one three-strain probiotic cultures was assessed duringPategras cheese ripening. Probiotics were inoculated into cheese-milk after a pre-incubationstep ? intended to improve their survival ? or directly as a lyophilised culture; control cheeseswithout probiotics were also obtained. pH of probiotic and control cheeses was similar, exceptin probiotic cheeses containing the strain Lb. acidophilus B or the mixed culture. In these cases,the probiotic cheeses were more acid than their respective control cheeses. All the probioticstested maintained counts above 107 cfu/g during the shelf-life settled for the product. Strains ofthe Lb. casei group: Lb. paracasei, Lb. casei and Lb. rhamnosus reached and kept the highestcell concentration during cheese ripening, followed by Lb. acidophilus and bifidobacteria. Thedirect addition of the probiotic cultures was more efficient than their inoculation after a preincubationstep, for all the probiotics assayed. We have provided evidence that support the useof Pategras cheese as a performing food-based vehicle for probiotic bacteria.